A study on the beneficial effect of advocating prophylactic spaying of young nulliparous bitches to prevent pyometra - Sharveihn Sathindren; Suryo Kuncorojakti; Suzanita Utama; Tita Damayanti Lestari; Wiwik Misaco Yuniarti (Ovozoa: Journal of Animal Reproduction, 2025)
This study aimed to evaluate the potential benefits of advocating elective spaying (ES) in young nulliparous bitches as a preventive measure for pyometra, a severe and potentially life-threatening condition. Specifically, the study examined whether elective spaying, which eliminates the risk of pyometra and its associated complications, offers significant advantages over the treatment of pyometra once it develops. Generally, the short- and long-term risks associated with elective spaying are minimal when compared to the significant complications and dangers posed by pyometra. A retrospective open-ended study was conducted, collecting data from veterinary clinics across Penang Island using a structured questionnaire. Information was gathered primarily from medical records and interviews with veterinarians and pet owners when data were missing or unclear in the records. The study compared 30 bitches of various breeds who underwent elective spaying with 30 bitches who underwent emergency ovariohysterectomy (EOH) due to pyometra. A standard set of outcomes was evaluated to assess and compare complications. The results showed that the elective spaying group experienced only minor or trivial complications, and owners incurred significantly lower costs compared to those whose bitches underwent emergency surgery for pyometra, which was associated with more severe complications and substantially higher costs. Based on these findings, the study concluded that elective spaying is a safe and cost-effective prophylactic measure against pyometra.